Surface condensation risk evaluation in light steel framing walls using ISO 13788:2012 - Daniela Martins, Paula; Gomes, Adriano; Miranda Lage, Carmem (Latin American Journal of Energy Research, 2025)
In recent years, Light Steel Framing (LSF) system has been increasing in Brazil. Despite numerous advantages when compared with the conventional construction system, such as the agility of the construction process, when inadequately designed, buildings can have their hygrothermal behavior penalized. Pathologies, such as surface condensation, can lead to degradation of the building envelope, and compromise indoor air quality. Thus, the objective of this paper is to evaluate the risk of surface condensation in a specific type of LSF system envelope, in an artificially conditioned environment, in bioclimatic zones 1 and 2 of Brazil. The evaluation uses the methodology described in the ISO 13788 (2012) standard. The methodology employed in this study consists of the conduction of computational simulations of a vertical enclosure within the LSF system using the THERM software. The evaluated configuration presented a risk of surface condensation in both regions. Among the strategies to reduce the effects of thermal bridges and the consequent risk of condensation in the panels, the one that presented the best results is the application of EPS thermal break strips.